Making complex things simpler: modern tools to edit the plant genome - N. E. Zlobin; V. V. Ternovoy; N. A. Grebenkina; V. V. Taranov (Вавиловский журнал генетики и селекции, 2017)
There are several technologies for plant genome editing, of which the most simple and universal is CRISPR/Cas. Currently, this technology is widely used for gene knockout, deleting genome fragments and inserting exogenous sequences in the plant genome. For each of these applications, many different types of genetic tools have been developed that are used by various research groups to solve specific problems. The CRISPR/Cas technology for plant genome editing is at an early stage of optimization, which is reflected by the ongoing search for the most effective, simple and flexible techniques. As a result, experimental work has to be preceded by a rather long and laborious process of selecting a genetic tool that will be optimal for a specific experimental task. In our review we describe the main variants of the CRISPR/Cas technology used to edit a plant genome. We classify them in terms of experimental tasks solved, major components and technology performance. In the first half of the review a detailed description of two major components of CRISPR/Cas technology – nuclease and guide RNA – is given, the effect of structural features of these elements on editing efficiency is analyzed. Experimental data on the relationship between editing efficiency and nucleotide sequence of guide RNA are generalized. We also give the characteristic for different variants of nucleases used for plant genome editing and discuss their benefits for different experimental purposes. In the second half of the review various strategies for expression of CRISPR/Cas elements in plant cells, in particular, advantages and disadvantages of stable transformation and transient expression, are discussed. The effect of various regulatory elements of genes encoding nuclease and guide RNA on editing efficiency is described. Special emphasis is placed on the techniques of increasing targeted gene replacement efficiency.